Direito fundamental à vida e ao aborto a partir de uma perspectiva constitucional, de gênero e da criminologia - Melo, Mônica de (2018)
This doctorate thesis defends the unconstitutionality of criminal treatment of abortion in Brazil by overstepping women’s human dignity and their fundamental constitutional rights to a worthy life, freedom, self-determination, difference, privacy and intimacy. It is necessary to interpret thought the constitution, keeping the hypotheses of abortion currently foreseen in the Penal Code. Abortion criminalization also violates the secularity of the state and protection of human rights international system, which Brazil is included, by bringing the duty to review the existing criminal legislation. Gender discrimination strongly operates in the sense of articulating a law that aimed to control the sexuality and on women´s reproductive health care, by preventing them from making moral choices with autonomy and responsibility. The abortion criminalization does not go through the rule of proportionality as it is not suitable, necessary and proportionate in a strict sense. It does not prevent the expressive realization of abortions having more effective and less restricted means of preventing abortions and protecting the life of unborn child. More over the analysis of secondary criminalization demonstrates the ineffectively of primary criminalization that operates, in this case, only to bring more pain and suffering beyond of what already causes the choice for the accomplishment of abortion. It is possible to implement a strategy in which abortion is allowed by weighting between the right to life and the fundamental rights of women